The Effect of Behavioral Propensity on Financial Risk Tolerance among Investor: The Role of Religiosity as a Moderating Variable - William Christhoper; Werner R. Murhadi; Endang Ernawati (Journal of Business & Banking, 2025)
This research aims to examine the effect of behavioral propensities variables that included propensity for regret, propensity for trust, happiness in life, propensity to attribute success to luck, propensity for overconfidence, and propensity for social interaction, on the variable of financial risk tolerance, as well as the moderating effect of religiosity. This study employs a quantitative approach using SEM (Structural Equation Modelling) analysis methods. This research was conducted by distributing questionnaires to investors aged 17 and above in Surabaya. The findings indicate that propensity for trust and propensity for social interaction significantly influence financial risk tolerance. However, propensity for regret, happiness in life, propensity to attribute success to luck, and propensity for overconfidence do not affect financial risk tolerance. Furthermore, regarding the moderating variable, religiosity influences all six behavioral propensity variables— propensity for regret, propensity for trust, happiness in life, propensity to attribute success to luck, propensity for overconfidence, and propensity for social interaction—toward financial risk tolerance.